Function-Based Intervention Plans: What and How to Teach. (December 2017) - Liaupsin, Carl J.; Cooper, Justin T.
Most function-based intervention plans (FBIP) discuss what to teach, but often fail to address effective methods for teaching the skills addressed in the plan. This article discusses the various parts of the FBIP plan that may require teaching and provides potential instructional approaches for teaching the components of the FBIP to students and others.